Religion, Cultural Elements and the Stock Price Crash Risk: a Test of Alternative and Complementary Theory - Abbas Ghodrati Zoeram; Mojtaba Alifamian; Soheyla Teymoorpoor (Iranian Journal of Accounting, Auditing & Finance)
As one of the most critical issues widely discussed in financial studies, the stock price crash is affected by different factors. Despite the importance of this issue for shareholders and investors, the behavioral characteristics of managers responsible for preparing financial statements have not been considered recently. Among those characteristics, the religion and culture of management have been mentioned in this research. Accordingly, the study examines the effect of managers' religion (replacement or complementary effect) and culture on the stock price crash risk in companies listed consistently on the stock exchange until the end of 2019. Therefore, in order to measure the stock price crash risk, two criteria consisting of negative skewness of stock return and down-to-up volatility have been applied. Hofstede's (2001) questionnaire was used to measure culture, and Li and Cai (2016) model was used to measure religion. Then, the results were analyzed by using multivariate regression models. Findings indicate that among the dimensions of culture, the uncertainty avoidance dimension has a negative effect. The dimension of individualism positively affects the stock price crash risk. The dimensions, including power distance and masculinity, do not affect the stock price crash risk. The negative impact of uncertainty avoidance means that conservative risk-averse managers do not make decisions in uncertain conditions. Because they are less inclined to accumulate bad news, they might reduce the stock price crash risk. On the other hand, the positive effect of individualism on the stock price crash risk shows that individualistic managers who do not consult with others about their decisions and insist on their wrong decisions ignore the negative consequences of harmful investments with excessive trust in their decisions and lead to the accumulation of losses in the company and consequently increasing stock price crash risk.   The results also show religion's negative and significant effect on the stock price crash risk. Religion reduces the risk of falling stock prices by reducing opportunism and agency problems. In addition, according to the complementarity theory, the sensitivity analysis results show that corporate governance exacerbates the negative relationship between religion and stock price crash risk of companies.